Prenatal phthalate exposure and anogenital distance in infants at 12 months - Kim N. Cajachagua-Torres; Nicole B. Salvi; Eunsil Seok; Yuyan Wang; Mengling Liu; Kurunthachalam Kannan; Linda G. Kahn; Leonardo Trasande; Akhgar Ghassabian (Environment International)
Objective: Anogenital distance (AGD) is a postnatal marker of in utero exposure to androgens and anti-androgens, and a predictor of reproductive health. We examined the association between gestational exposure to phthalates and AGD in male and female infants. Methods: In 506 mother-infant pairs (276 males, 230 females), we measured urinary concentrations of phthalate metabolites at < 18 and 18–25 weeks of gestation and AGD at child age 12.9 months (95 % range 11.4–21.1). Phthalate metabolite concentrations were adjusted for urinary dilution, averaged, and natural log-transformed. We measured anus-clitoris distance (AGDac) and anus-fourchette distance (AGDaf) in females, and anus-scrotum distance, anus-penis distance, and penile width in males. We used linear regression and partial-linear single-index (PLSI) models to examine associations between phthalates and AGD as single pollutants and in mixture. Results: Fifty-eight percent of mothers were Hispanic, followed by 27 % non-Hispanic White. Higher exposures to ∑di-isononyl(phthalate) (∑DiNP) was associated with longer AGDaf [1.28 mm (95 % confidence interval [CI]: 0.52, 2.03) and 0.97 mm (95 %CI: 0.25, 1.69), respectively]. Higher exposures to ∑di(2-ethylhexyl)phthalate (∑DEHP) was associated with longer AGDac [2.80 mm (95 %CI: 1.17, 4.44), and 1.90 mm (95 %CI: 0.76, 3.04), respectively]. No association was observed between phthalate metabolites and AGD in males after multiple testing correction. In mixture analyses, ∑DiNP and ∑DEHP were the main contributors to longer AGD in females. We also detected an interaction between ∑DiNP and ∑DEHP in association with AGD in females. Conclusion: Early pregnancy phthalate exposure was associated with longer AGD in female infants. Biological mechanisms underlying these associations should be further investigated.